2017
DOI: 10.1016/j.cortex.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural differences in the neural correlates of specific and general recognition

Abstract: Research suggests that culture influences how people perceive the world, which extends to memory specificity, or how much perceptual detail is remembered. The present study investigated cross-cultural differences (Americans vs. East Asians) at the time of encoding in the neural correlates of specific vs. general memory formation. Participants encoded photos of everyday items in the scanner and 48 hours later completed a surprise recognition test. The recognition test consisted of same (i.e., previously seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 62 publications
(87 reference statements)
3
31
2
Order By: Relevance
“…There were no differences in general memory (correctly remembering items as same or remembering a same item as similar ) across Americans and East Asians. On the other hand, Paige et al (2017) found no significant differences in specific memory between Americans and East Asians. Taken together, the results are inconsistent, as one set of instructions (Millar et al 2013) showed a cultural difference in specific memory across Americans and East Asians, but the other set of instructions (Paige et al 2017) did not.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…There were no differences in general memory (correctly remembering items as same or remembering a same item as similar ) across Americans and East Asians. On the other hand, Paige et al (2017) found no significant differences in specific memory between Americans and East Asians. Taken together, the results are inconsistent, as one set of instructions (Millar et al 2013) showed a cultural difference in specific memory across Americans and East Asians, but the other set of instructions (Paige et al 2017) did not.…”
Section: Introductionmentioning
confidence: 59%
“…In both Millar et al (2013) and Paige et al (2017), the authors assessed cross-cultural differences in memory specificity for everyday objects. The general structure for each study was the same.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from a subset of these participants were analyzed in a univariate analysis published separately (Paige et al , 2017b). …”
Section: Acknowledgementsmentioning
confidence: 99%